2016
DOI: 10.1007/s00127-016-1241-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders among adolescents from Lebanon: prevalence, correlates, and treatment gap

Abstract: A clear treatment gap is evident with a high 30-day prevalence of psychiatric disorders among adolescents in Beirut coupled with a very low percentage seeking treatment. Scaling up mental health services and addressing potential barriers to seeking care would be important to close this gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 37 publications
7
73
4
Order By: Relevance
“…We found that for 22.5 % of students who were rated as high achievers, 30.7 % of medium rated achievers and 41.2 % of low school achievers, parents refused to participate in the study. Since low school achievement has been found to be associated with more emotional and behavioral problems [46], these response rates should be considered when interpreting the results. As expected, and as a consequence of the higher response rates in locality 3, we found there more students with low achievement and with higher mean TDS than in other localities, where response rates were lower and where low achievers were less likely to participate.…”
Section: Discussionmentioning
confidence: 99%
“…We found that for 22.5 % of students who were rated as high achievers, 30.7 % of medium rated achievers and 41.2 % of low school achievers, parents refused to participate in the study. Since low school achievement has been found to be associated with more emotional and behavioral problems [46], these response rates should be considered when interpreting the results. As expected, and as a consequence of the higher response rates in locality 3, we found there more students with low achievement and with higher mean TDS than in other localities, where response rates were lower and where low achievers were less likely to participate.…”
Section: Discussionmentioning
confidence: 99%
“…Quality control was assured through call-backs of 10% of the recruited households selected at random to verify the accuracy of the retrieved information. Further details on the study protocol can be found elsewhere [13]. …”
Section: Methodsmentioning
confidence: 99%
“…The scarcity in research data is one of the major contributors to a lack of mental health resources in Lebanon (and in the region) as epidemiological evidence is usually the impetus behind developing mental health awareness and funding treatment resources [12]. The Beirut Epidemiological Investigation of the Psychiatric Status of Youth (BEI-PSY) is the first general population-based survey study to investigate the prevalence, correlates, and treatment seeking behaviors related to psychiatric disorders among adolescents in Lebanon [13]. The specific aims of this paper include: (1) examining the sociodemographic characteristics of adolescents with ADHD compared to adolescents with other psychiatric illnesses and healthy subjects; and (2) investigating the correlates of having the diagnosis of ADHD compared to not having the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, many Arab countries have witnessed wars, conflicts, and major social and geopolitical changes that have negatively influenced the mental health of their people (1,2). As a result, many researchers examined published literature on the topic, but have focused on specific disorders, such as autism (3), bipolar disorders (4), and substance use/abuse (5).…”
Section: Introductionmentioning
confidence: 99%